Ekologis Hutan Novel "Si Anak Pemberani" Karya Tere Liye: Kajian Ekokritik Garrard - Juanda, Juanda (Dinamika: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2025)
In literature, the environment is significant not just as a location for stories but also as a character in and of itself. In line with Garrard's ecocritical theory, this study looks at the following ecological elements: pollution, wilderness, apocalypse, dwelling, animals, and earth. In order to assess the ecological elements of Tere Liye's 2018 novel “Si Anak Pemberani”, which was released by Republika Publisher, this study uses a qualitative descriptive design. The research implemented a literature review as the data collection method by thoroughly analyzing and extracting relevant ecological themes from the novel. Thematic analysis with an interactive model was used for data analysis, encompassing three stages: data condensation, data display, and conclusions drawing/verifying through the NVivo R1 2020 program. The results reveal an exploration of diverse and profound ecological aspects within the novel. These aspects encompass pollution, which portrays the adverse effects of human activities on nature; wilderness, as a vital source of life and harmony that is susceptible to destruction; natural disasters resulting from ecological disturbances; settlements, which showcase residents' interaction with their surroundings; animals, which actively engage with the environment; and the Earth, which serves as the bedrock for comprehending human beings' relationship with the planet. This research demonstrates how literature can effectively educate and improve environmental awareness among junior and senior high school students. This research highlights the importance of an ecocritical approach in literary studies, particularly in the context of Indonesia which faces ecological challenges for legal policymakers.Keywords: ecocriticism, environmentalism, forest, novelABSTRAKDalam sastra, lingkungan menjadi penting bukan hanya sebagai lokasi cerita, tetapi juga sebagai karakter dalam cerita itu sendiri. Sejalan dengan teori ekokritik Garrard, penelitian ini melihat unsur-unsur ekologi berikut: polusi, hutan belantara, bencana, permukiman, binatang, dan bumi. Untuk mengkaji unsur-unsur ekologi dalam novel “Si Anak Pemberani” karya Tere Liye tahun 2018 yang diterbitkan oleh Penerbit Republika, penelitian  menggunakan desain deskriptif kualitatif dengan teknik studi pustaka. Novel dibaca dan diteliti secara menyeluruh untuk memahami dan mengekstrak tema-tema ekologis yang relevan. Penelitian menggunakan teknik analisis tematik dengan model interaktif, yang melibatkan tiga tahap: data display, data condensation, dan conclusions drawing/verifying dengan bantuan program NVivo R1 2020. Temuan menunjukkan bahwa novel ini mengeksplorasi berbagai aspek ekologis yang mendalam dan beragam, seperti polusi, sebagai dampak negatif aktivitas manusia; hutan belantara, sebagai sumber kehidupan dan harmoni yang rentan terhadap kerusakan; bencana alam sebagai konsekuensi dari gangguan ekologis; pemukiman, yang menyoroti interaksi penduduk dengan tanah dan lingkungan mereka; binatang, yang diperkenalkan sebagai entitas yang aktif berinteraksi dengan lingkungan; dan bumi, yang dihadirkan sebagai fondasi untuk memahami hubungan manusia dengan planet. Penelitian ini memberikan kontribusi bahwa sastra dapat mendidik dan meningkatkan kesadaran lingkungan, khususnya dalam lingkup siswa SMP dan SMA. Penelitian ini menunjukkan pentingnya pendekatan ekokritik dalam studi sastra, terutama dalam konteks Indonesia yang menghadapi tantangan ekologis bagi pembuat kebijakan hukum.Kata kunci: ekokritik, hutan, novel, peduli lingkungan